2016
DOI: 10.1016/j.fertnstert.2015.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity or environment: effects of migration on ovarian reserve among Bangladeshi women in the United Kingdom

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 89 publications
3
44
0
Order By: Relevance
“…We have previously reported that women of Bangladeshi originthose still living in Bangladesh and migrant women who moved to London during adulthood -had significantly earlier ages at menopause compared to London women of European origin [23]. These data are confirmed by Begum et al [24] who found that age-matched Bangladeshi sedentees and adult migrants had levels of inhibin B, AMH, FSH, and E 2 that demonstrated an earlier age-related decline in ovarian reserve when compared to women of European origin.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…We have previously reported that women of Bangladeshi originthose still living in Bangladesh and migrant women who moved to London during adulthood -had significantly earlier ages at menopause compared to London women of European origin [23]. These data are confirmed by Begum et al [24] who found that age-matched Bangladeshi sedentees and adult migrants had levels of inhibin B, AMH, FSH, and E 2 that demonstrated an earlier age-related decline in ovarian reserve when compared to women of European origin.…”
Section: Introductionsupporting
confidence: 78%
“…Age at menopause and symptoms of the menopause are known to vary according to ethnicity [9,[25][26][27]. Murphy et al [23] previously found that Bangladeshi women in this sample had an earlier age at menopause compared to European women, while Begum et al [24] found that Bangladeshi sedentees and adult migrants had levels of hormones that confirmed an earlier process of reproductive ageing and an earlier decline in ovarian reserve. The significant differences between ethnic groups in their experience of hot flushes in the past 2 weeks may therefore be a reflection of variation in their relative ages at the menopausal transition.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Ecological, rather than evolutionary, explanations have generally been the focus for understanding variation in ages at menopause across populations (Sievert, ). This is due, in part, to evidence of a relationship between difficult environments during early childhood and an earlier age at menopause (Begum et al, ; Elias et al, ; Murphy et al, ), and also to the lack of variation in age at menopause across ethnic groups when childhood environments are relatively the same (Gold et al, ; Sievert et al, ).Inter‐ and intrapopulation variation has been documented in levels of reproductive hormones (Clancy et al, ; Ellison, Panter‐Brick, Lipson, & O'Rourke, ), age at menarche (Azcorra et al, ; Eveleth and Tanner, ), and age at natural menopause. For example, the mean prospective age at natural menopause in the U.S. is 52.5 years (Gold et al, ), while the within‐population timing of menopause can range from the early 40s to the late 50s (McKinlay, Brambilla, & Posner, ; Sievert, ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior study findings highlight more broadly the impact of early life environments on subsequent reproductive health outcomes. For example, using a novel study design, women who grew up in Sylhet, Bangladesh were shown to have hormonal profiles consistent with lower ovarian reserve and reduced fertility compared to their Bangladeshi counterparts who migrated to Britain as children (versus as adults) as well as to other European-born women who grew up in Britain [61,62]. This suggests that early life adversity exposures in Bangladeshi neighborhoods, possibly reflecting exposures to nutritional stress, infectious disease, or other yet unidentified stressors, may detrimentally impact adulthood reproductive health outcomes.…”
Section: Discussionmentioning
confidence: 99%